Post Traumatic Total Aniridia along with Superior Subconjunctival Dislocation of Posterior Chamber Intraocular Lens: A Rare Case Report (Journal of Nobel Medical College, 2025)
To report a case of post traumatic total aniridia along with superior subconjunctival dislocation of posterior chamber intraocular lens.  A 55-year-old man who underwent small incision cataract surgery with posterior chamber intraocular lens 2 years back had traumatic total aniridia along with superior subconjunctival dislocation of intraocular lens to his right eye with cow’s horn. The patient was managed with surgical extraction of lens and iris from the subconjunctival space in conjunction with suturing in the incision site (wound dehiscence) was done.  Patient was planned for secondary intraocular lens implantation. It is quite challenging to manage such a case. Despite proper surgical management visual outcomes are always guarded in such patients. Extrusion of intraocular lens (IOL) with total aniridia in pseudophakic eyes after trauma has rarely been reported in literature.